(untitled) (City: History, Culture, Society, 2023)
Valentyna Radzymovska (1886–1953) is a prime example of a woman who excelled in science, politics, and social life in the women-oppressed society of the early 20th century. Radzymovska is well-known as a biochemistry, physiology, and cell biology researcher, as well as a physician and university professor. She also participated in the Ukrainian national movement and the 1917–1921 Ukrainian Revolution. The majority of her biography was written by Ukrainian diaspora authors who lacked access to Kyiv local archives and sources, and their inconsistencies and errors were then transferred to new publications by independent Ukraine researchers. In this study, archival materials, contemporary newspapers, memoirs, and other sources were analyzed to advance the reconstruction of Valentyna Radzymovska’s biography. Contrary to previous reports, she participated in Ukrainian Revolution events, ran for the Kyiv City Duma on the Ukrainian Social Democrat election list, served as the head of the Kyiv city Ukrainian Council, and her apartment became a center of political life. During the trial of “Union for the Freedom of Ukraine”, the Radzymovska political archive-criminal case of 1929–1930 was presented for the first time. The study of Radzymovska’s scientific environment revealed her research positions and established her student circle. Already published and newly described details of Radzymovska’s personal life enable us to characterize her as a communicative, intelligent, and passionate woman who, despite her exceptional political skills and difficult life choices, remained humane to the end.